Biotechnological Potential of Seaweeds from Bahia, Brazil: Metabolomic insights, Photoprotection and Antioxidant Activity - Santana, Keila Almeida; da Silva, Isadora de Jesus; Ribeiro, Victor Pena; de Castro Nunes, José Marcos; Debonsi, Hosana Maria; Castro‐Gamboa, Ian [UNESP]; Gaspar, Lorena Rigo; dos Santos, Gustavo Souza [UNESP]; de Freitas Santos Júnior, Aníbal (Wiley, 2025)
Seaweeds have wide biotechnological applications. This study evaluated the chemical profile, photoprotective, and antioxidant potential of Padina sp., Caulerpa sertularioides, and Solieria filiformis collected in Bahia, Brazil. Chemical characterization by gas chromatography-mass spectrometry (GC-MS) and proton nuclear magnetic resonance (1H NMR) confirmed fucosterol in Padina sp., β-sitosterol in C. sertularioides, and cholesterol in S. filiformis alongside fatty acids and aromatic metabolites; multivariate analyses supported species-specific chemical patterns. The extracts exhibited ultraviolet (UV) absorption, in specific the UVA range, and were nonirritant in the Organization for Economic Co-operation and Development (OECD) Test Guideline (TG) 491 assay. In human keratinocytes (HaCaT), C. sertularioides reduced UV-induced reactive oxygen species (ROS) by 75%, whereas Padina sp. and S. filiformis achieved 42% reduction. Conversely, extracts exhibited photodegradation in the UV region and phototoxic potential in the OECD TG 432 (3T3 neutral red uptake, NRU) assay. Because these trials used complex crude extracts, future studies should optimize the extraction process, fractionate bioactive-rich fractions, and isolate key compounds. These results highlight Brazilian algae as promising sources of new compounds and serve as a starting point for further investigations.